Constraining Martian Regolith and Vortex Parameters From Combined Seismic and Meteorological Measurements. Issue 2 (18th February 2021) - Murdoch, N.; Spiga, A.; Lorenz, R.; Garcia, R. F.; Perrin, C.; Widmer‐Schnidrig, R.; Rodriguez, S.; Compaire, N.; Warner, N. H.; Mimoun, D.; Banfield, D.; Lognonné, P.; et al.
Abstract: The InSight mission landed on Mars in November 2018 and has since observed multiple convective vortices with both the high performance barometer and the low‐noise seismometer SEIS that has unprecedented sensitivity. Here, we present a new method that uses the simultaneous pressure and seismic measurements of convective vortices to place constraints on the elastic properties of the Martian subsurface and the Martian vortex properties, while also allowing a reconstruction of the convective vortex trajectories. From data filtered in the (0.02–0.3 Hz) frequency band, we estimate that the mean value of η ( η  =  E /[1 −  ν 2 ], where E is the Young's modulus and ν is the Poisson's ratio) of the Martian ground in the region around SEIS is 239 ± 140 MPa. In addition, we suggest that the previously reported paucity of vortex seismic observations to the west of InSight may be due to the fact that the ground is harder to the west than to the east, consistent with geomorphological surface interpretations. Plain Language Summary: In 2018, the InSight mission placed a seismic instrument on the surface of Mars in order to measure the motion of the Martian ground. As on Earth, there are fluctuations of pressure in the Martian atmosphere caused by small local variations in the atmospheric weight. Whirlwinds, for example, have a lower pressure in their center and they pull up the ground (like a vacuum cleaner). Such changes in pressure deform the elastic Martian ground and the InSight seismic instrument is sensitive enough to measure these deformations. We present a new method that uses the InSight pressure and seismic measurements of whirlwinds in order to determine how hard or soft the Martian ground is. We are also able to estimate the path that the whirlwinds follow as they pass by InSight. We find that the surface material just under InSight has elastic properties similar to dense gravel, but that the whirlwinds detected by the seismic instrument are not in the same places as the whirlwinds tracks observed from space. Our results suggest that the ground is harder to the west and, consequently, that it is more difficult for whirlwinds to deform the ground and create a seismic signal in that region. Key Points: Elastic properties of the Martian subsurface can be constrained using simultaneous pressure and seismic measurements of convective vortices Our modeling can also be used to constrain Martian convective vortex properties and to reconstruct the vortex trajectories The results indicate that the Martian ground may be harder to the west of InSight, consistent with geomorphological surface interpretations